(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The story of transformation in Cuban economy and society through tourism growth, identifying its twin functions as source of significant economic motor and social changer, is revealed in this article. How tourism has emerged to be among the country’s sources of sizeable revenue that translates into growth of GDP, job creation, and infrastructure expansion is explained by this article. Simultaneously, it measures the social impact, which involves cultural exchange, shifting social norms, and increasing economic inequality. Scholarship sets the government policies that have shaped the sector, foreign investment, and the challenge of balancing economic gains with societal cohesion. Drawing on the mixed bag of statistical data, case research, and policy assessments, the article aims to come up with a wide perception of the mechanisms through which tourism reordered the modern Cuba. Lastly, it determines whether such transformation has promoted sustainable economic progress or exacerbated long-existing inequalities in Cuban society.